Translation, back-translation and cultural adaptation of the 8-item Stigma Scale for Chronic Illness to Portuguese - Brancucci, Rosana Tieka Miyazaki; Natan, Marcio Lima Pontes; Silva, Aline Vitali da; Oliveira, Arao Belitardo de; Mercante, Juliane Prieto Peres (Headache Medicine, 2019)
Cultural diversity limits cross cultural understanding of diseases. Stigma has been studied in neurological disorders, chronic pain and migraine, but instruments are not available in Portuguese. We aimed to translate the 8-item Stigma Scale for Chronic Illness to Portuguese. Methods: We followed the 5 steps advised by guidelines for transcultural validation. Results: Translation, backtranslation and cultural validation has been performed following the 5 steps, and a final version of the instrument was achieved. Discussion/Conclusion : Stigma is an important issue in migraine management. Measurement of stigma in headache sufferers in Brazil may be started. The final version of the instrument is provided.